Solusi Numerik Model SITA Menggunakan Metode Runge Kutta Fehlberg Untuk Memprediksi Penyebaran Penyakit HIV/AIDS Di Provinsi Maluku - Serlaloy, Marshanda Nalurita; Rijoly, Monalisa E.; Leleury, Zeth Arthur (Universitas Cokroaminoto Palopo, 2024)
This research aims to predict the spread of HIV/AIDS in Maluku Province using the Runge Kutta Fehlberg method. The mathematical model of the spread of HIV/AIDS disease is in the form of a system of differential equations that includes Susceptible (S) variable, namely individuals who are healthy but vulnerable to being infected with the HIV virus, Infected (I) variable namely individuals who are infected with the HIV virus, Treatment (T) variable namely individuals who receive antiretroviral therapy and AIDS (A) variable namely individuals who contract AIDS disease used as initial values. Values as parameter values are solved numerically using the Runge Kutta Fehlberg method performed as many as 10 iterations with an interval time of using data from Maluku Provincial Health Office and BPS-Statistics Indonesia from 2013 to 2022. Based on the data obtained, the average value of the data is used as the initial value where . The initial values and parameter values are substituted into the numerical solution and simulated using software Matlab as tools. The rate value of each class for the next 10 years is for the class rate of individuals susceptible to HIV infection (S) of 1.757.102 people, for the class rate of HIV-infected individuals (I) of 2482 people, for the class rate of individuals receiving antiretroviral treatment (ARV) (T) of 1516 people and for the class rate of individuals with AIDS (A) of 555 people. This means that the (S) and (T) populations will decrease over the next 10 years while the (I) and (A) populations will increase over the next 10 years.